Effect of Supplementation of Zinc Methionine in Productive Performance and Eggs Quality Traits Laying Hens - Majeed, Noor Talib; Razouqi, Ali Jawad (Journal of agricultural, environmental and veterinary sciences, 2020)
The study was conducted in the field of poultry at the Department of Animal Production/ College of Agriculture- University of Diyala from the period from 21- 1 to 21- 4- 2019. It aimed to study the effect of adding different levels of zinc methionine to the diet in some productive qualities of laying hens. The researcher used 144 chickens (Lohmann Brown) at the age of 21 weeks for the experiment. Randomly distributed to four treatments and zinc methionine was added at a rate of 0, 30, 60, and 90 mg/ kg of diet for the four treatments (T1, T2, T3, T4), respectively. The results of the statistical analysis of the experimtal data showed a significant increase (P<0.01) in egg production rate and egg weight in T2, T3, and T4 treatments compared with control treatment. There was no significant effect of supplementation factors on the daily feed intake rate, but it significantly improved (P<0.01(feed conversion efficiency. The addition of zinc methionine to the diet significantly improved (P<0.01(represented as qualitative characteristics of the thickness and weight of the crust, and the addition of zinc methionine in the diet of laying hens by 30, 60, and 90 mg/ kg of diet improved significantly. It is concluded from this study that the addition of zinc methionine at the level of 60, 90 mg/ kg of diet yielded showed best results in productive performance, qualitative qualities of laying hens.